The Economic Crisis and its Impact on International and Greek Education - Bouzakis, Siphis; Diplari, Christina (Études helléniques / Hellenic Studies, 2012)
The purpose of this article is to study the current financial crisis and its impact on Greek education. After the Metapolitefsi (fall of the dictatorship) of 1974, with the contribution of a calm political landscape, the country, pushed also by its integration into the European Economic Community in 1979 and the Economic and Monetary Union in 2002, will follow a more stable path to westernization / modernization, even in education sector, through successive reforms. These reforms are no longer overturned even if their application continues to meet resistance. The situation has been reversed since the advent of the financial crisis which, while preexisting, will break out the biennium 2009-2011 with the country’s appeal to the International Monetary Fund and to the support mechanisms of the European Union. After a brief reference to the impact of the crisis on international education, the article will focus on the Greek area where, as shown by researches, the crisis has brought about dramatic transformations in all areas of education (education budget cuts, teachers’ salary and pension cuts, school mergers and closures, reduction in teacher recruitment).